Developing domino card learning media for the fourth grade of elementary school students - Salsa Gitamayu; Husniati Husniati; Baiq Niswatul Khair (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
This research aims to produce quality domino card learning media products. This type of research is research and development with the ADDIE model. The ADDIE model consists of several stages, namely analysis, design, development, implementation, and evaluation. The test subjects in this study were six fourth-grade Elementary School students, SDN 08 Mataram Lombok Indonesia, with category two students with high ability, two people with medium ability, and two students with low ability. The research data were obtained using a media feasibility test, validation questionnaire for media experts, material experts, student response questionnaires, and teacher responses. Based on the trial results, it was obtained data on the results of student responses percentage of 94.3%, which were included in the